The Future of the Family - Rainwater, Lee; Smeeding, Timothy M.; Moynihan, Daniel P. (Daniel Patrick), 1927-2003 (Book collections on Project MUSE., 2004)
"This book takes stock of the state of the family in the United States today and addresses the ways in which public policy affects the family and vice versa."--Jacket